The Trump Phenomenon and the Racialization of American Politics - Serge Ricard (Revue LISA)
If very few observers across the Atlantic predicted that a reality-TV star would succeed the United States’ first African American President, there is today among commentators of the political scene a scramble for analysis of the rise of Donald J. Trump. His victory can no doubt be attributed to a conjunction of causes but one in particular deserves special attention: the racial factor. The Trump phenomenon was regarded as the elevation to the highest office of a political misfit when it was actually a return to normalcy in a historically racist society. Barack Obama’s election was atypical, not Trump’s. The following essay attempts to throw light on the permanence of the race factor in American society, its impact on the 2016 election, either by means of its unabashed activation or through a coded rhetoric, its centrality in the Trumpian discourse, the heyday of white nationalism under a President prone to stoking the flames of division and prejudice, together with the disquieting signs of a “new civil war” in a disunited nation.